Teacher’s Roles in Dangerous Minds Movie - Sitti Fitriawati (Sintuwu Maroso Journal of English Teaching, 2018)
The objective of this study is to find out the roles of teacher in dangerous mind movie. It focused on LouAnne Johnson as main character in the movie limited the interaction between teacher and students in the classroom. Descriptive qualitative was used as the research design. The Dangerous Minds movie is source of data in this research. In collecting the data, the researcher used documentation method. There are four roles of teacher in this movie: assessor; prompter, tutor, and observer. The most prominent role teacher character in this movie is prompter.Keywords: Dangerous Minds, roles of teacher, teacher as prompter, movieanalysis